Dysregulation of plasma circulating microRNAs in all-cause and cause-specific cancers: the Rotterdam Study - Yu Shuai; Xiaofang Zhang; Birgit D. A. Lavrijssen; M. Arfan Ikram; Rikje Ruiter; Bruno Stricker; Mohsen Ghanbari (BMC, 2024)
Abstract MicroRNAs (miRNAs) are small non-coding RNAs involved in post-transcriptional regulation of gene expression. Mounting evidence underscores the dysregulation of miRNAs to be associated with cancer development and progression by acting as tumour suppressors and oncogenes. However, their potential as biomarkers for early diagnosis of different cancers remains incompletely unraveled. We explored the relationship between plasma circulatory miRNAs and cancer risk within the population-based Rotterdam Study cohort. Plasma samples were collected at baseline (between 2002 and 2005) and miRNA levels were measured in 1,999 participants, including 169 prevalent cancer cases. The occurrence of cancer was assessed by continuous monitoring of medical records in 1,830 cancer-free participants until January 1, 2015. We assessed the association between incidence of five common cancers (blood, lung, breast, prostate, and colorectal) and 591 miRNAs well-expressed in plasma, using adjusted Cox proportional-hazards regression models. Our longitudinal analysis identified 13 miRNAs significantly associated with incident hematologic tumors surpassing the Bonferroni-corrected P < 8.46 × 10− 5, 12 of them (miR-6124, miR-6778-5p, miR-5196, miR-654-5p, miR-4478, miR-4430, miR-4534, miR-1915-3p, miR-4644, miR-4292, miR-7111-5p, and miR-6870-5p) were also associated with prevalent hematologic tumors in the cross-sectional analysis at the baseline. In-silico analyses of the putative target genes of 13 identified miRNAs highlighted relevant genes and pathways linked to hematologic tumors. While no significant miRNA association was found for other four studied cancers, two miRNAs (miR-3157-5p and miR-3912-5p) showed nominal association with incident of three different cancer types. Overall, this study indicates that plasma levels of several miRNAs are dysregulated in hematologic tumors, highlighting their potential as biomarkers for early diagnosis as well as being involved in the pathogenesis of blood cancers.